Pulmonary sarcoidosis - Deepak Talwar; Dhruv Talwar; Hariharan Iyer (Indian Journal of Rheumatology)
Pulmonary sarcoidosis is an enigma due to its similarities with many other diseases in terms of presentation and hence the disease may require repeated reconsideration and revision of diagnosis. It is largely a diagnosis of exclusion. In India, exclusion of tuberculosis (TB) in every new suspected case of pulmonary sarcoidosis is a colossal task due to overlapping features and the high burden of TB. However, pulmonary sarcoidosis may be associated with extrapulmonary organ involvement, and in such cases, diagnosis can be made with greater certainty. Once diagnosed, whether to treat or not, and with what agent, and for how long are questions unsettled despite 150 years of the disease being known to mankind. This is due to a lack of randomized controlled trials as well as a dissimilar natural course of the disease among patients with a similar clinicoradiological presentations. This makes a generalization about treatment impossible and hence, individualized decisions need to be made utilizing predictors of future worsening by multidisciplinary experts. Oral steroids form the core of treatment but longterm side effects of oral steroids ultimately dictate the use of steroidsparing agents and discontinuation of steroids once the disease stabilizes and the goals of treatment are achieved. Some patients with a benign course of sarcoidosis may not require any treatment. There remains a gap in our knowledge of sarcoidosis, especially in the context of India, as it features as a common cause of interstitial lung disease and a close differential of TB. We need to intervene before the condition worsens, as this may reduce the survival significantly. However, this is not always possible and more research including longitudinal studies are needed to define and understand the course of the disease.